Preoperative lumbar drainage placement for surgical cranioplasty - Giese, Henrik; Unterberg, Andreas; Beynon, Christopher (Journal of clinical neuroscience, 2018)
Objective - Intraoperative reduction of cerebrospinal fluid may be required in patients undergoing cranioplasty (CP) surgery, especially in the presence of bulging cranial defects. Direct cannulation of the frontal horn of the lateral ventricle is associated with risks such as intracerebral haemorrhage or postoperative leakage of cerebrospinal fluid. Here we report our initial experiences with preoperative lumbar drain (LD) placement for cranioplasty surgery in patients with bulging cranial defects. - Method - The medical records of patients who were treated with LD prior to CP surgery at our institution were retrospectively analysed. Pre-, intra- and postoperative modalities, complications and outcome parameters are described. - Results - A total of 14 patients (mean age 46years) were included in this analysis. The majority of patients had received decompressive craniectomy due to space-occupying cerebral infarction (64.3%) and traumatic brain injury (14.3%). CP was performed unilaterally with autologous bone graft in 93% of cases. No complications occurred during lumbar drainage placement and the grafts were implanted without the need of dural opening and ventricle puncture. LDs were maintained for an average of 17±15h (range, 1-48h). There were no LD related complications in the further course. - Conclusion - Our initial experiences demonstrate that preoperative LD placement facilitates CP in patients with bulging cranial defects requiring surgical cranioplasty. Intraoperative puncture of ventricles for reducing cerebrospinal fluid is avoided and therefore, the risk of intracerebral haemorrhage and brain damage is reduced. Further studies are needed to evaluate the advantages of this technique as an alternative to conventional methods of intraoperative CSF reduction.
Gesehen am 05.04.2019